Corrosion behavior of X80 pipeline steel local defect pits under static liquid film - Tan, Zhuowei; Wang, Zhenbo; Zhang, Shengzhu; Bai, Shuyu; Zhang, Dalei; Jin, Youhai; Xing, Shaohua (Scientific reports, 2021)
In this work, the corrosion electrochemical information under different thicknesses of liquid film was tested. The local corrosion development process of X80 steel under different thicknesses of liquid film was studied by combining the detection and analysis of scale and the matrix corrosion morphology. The corrosion was studied by EIS. The composition and microstructures of corrosion scale at different locations were detected by EDS and SEM, and the metal matrix was detected by 3D topography technology to analyze the local corrosion. The results show that a liquid film with a thickness greater than or equal to 1 mm has no effect on the mechanism of the corrosion process, but has a control effect on the corrosion rate and the time of each stage in corrosion. The corrosion process can be divided into two stages: in the early stage, the concentration of ions inside and outside ADP is the same, so the corrosion is uniform; in the later stage, due to the influence of CO 2 dissolution and mass transfer distance, the cathodic reaction is mainly outside ADP and the anodic reaction is mainly inside ADP. In addition, corrosion acidification occurs in ADP, which enhances the corrosion process in ADP.